The Effects of Napping on Wakefulness and Endurance Performance in Athletes: A Randomized Crossover Study - Felix Willmer; Claire Reuter; Stephan Pramsohler; Martin Faulhaber; Anja Burkhardt; Nikolaus Netzer (Life, 2023)
Background: Athletes often experience poor sleep quality due to stress, altitude exposure, travel across different time zones, and pre-competition nervousness. Coaches use daytime naps to counteract the negative effects of fragmented nighttime sleep. Napping before competitions has also been used to enhance performance in athletes without sleep problems, with mixed results in previous studies, particularly for endurance performance. Thus, we investigated the effects of napping after partial sleep deprivation (PSD) on endurance performance and wakefulness in athletes. Methods: We recruited 12 healthy and trained participants (seven female and five male) for a randomized crossover study design. The participants underwent two test sessions: a five-hour night of sleep without a nap (noNap) and a five-hour night of sleep with a 30-min nap opportunity (Nap30). Participants recorded their sleep-wake rhythm one week before and during the study using the Consensus Sleep Diary-Core and the Morningness–Eveningness Questionnaire to examine their circadian rhythm type. We quantified PSD and the nap with pupillography (pupil unrest index, PUI), a subjective level of sleepiness questionnaire (Karolinska Sleepiness Scale, KSS), and polysomnography. After each night, participants performed a maximal cycling ergometry test to determine time to exhaustion (TTE) and maximal oxygen uptake (VO 2max). Results: Participants had an average sleep duration of 7.2 ± 0.7 h and were identified as moderately morning types (n = 5), neither type (n = 5), and moderately evening types (n = 2). There was a significant difference in both sleepiness parameters between the two conditions, with the PUI (p = 0.015) and KSS (p ≤ 0.01) significantly decreased at 5 h and nap compared with only 5 h of sleep. The PUI (p ≤ 0.01) and KSS (p ≤ 0.01) decreased significantly from before to after the nap. However, there was no significant difference in physical exercise test results between the conditions for TTE (p = 0.367) or VO 2max (p = 0.308). Conclusions: Our results suggest that napping after light PSD does not significantly influence endurance performance. We conclude that aerobic performance is a multidimensional construct, and napping after PSD may not enhance it. However, napping is an effective method to increase wakefulness and vigilance, which can be beneficial for sports competitions.